Faktor-Faktor Yang Mempengaruhi Profitabilitas Perbankan (Studi pada Bank Umum Go Public Yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Umamatul Khoeriyah; Roni Roni; Syariefful Ikhwan; Roby Setiadi; Mohammad Badrun Zaman (Journal of Accounting and Finance (JACFIN), 2019)
This study aims to analyze the influence of Capital Adequacy Ratio (CAR), Operational Cost to Operating Income (BOPO), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Net Interest Margin (NIM), to Banking Profitability (ROA). The population that became the object in this study is a public bank going public listed on the Indonesia Stock Exchange period 2011-2015. The number of samples used are 25 public banks going public listed on the Indonesia Stock Exchange. The sample of research is taken by purposive sampling with certain criterion that is banking company belonging to commercial bank go public, and bank have published its financial report in year 2011-2015. The method used in this research is to use multiple regression analysis with hypothesis test that is t test and F test. Before using multiple regression analysis, classical assumption test is done first. From the result of hypothesis test simultaneously (F test) indicate that CAR, BOPO, LDR, NPL, NIM, have significant influence to bank profitability at commercial bank go public with level signifikan signifikan 0.000. While based on partial hypothesis test result (t test) at commercial bank go public show that variable of CAR, BOPO, NPL, NIM, have significant effect to bank profitability. While the LDR variable is not significant to banking profitability. The adjusted R2 value in the regression model of the bank go public is obtained at 0.519. It shows that big influence of independent variable that is CAR, BOPO, LDR, NPL, NIM to dependent variable (ROA) equal to 51,9% while the rest of 48,1% influenced by other factor. Moreover the value of R2 is 0.539. If the value of R2 is closer to 1 then the independent variables (CAR, BOPO, LDR, NPL, NIM) are more powerful in explaining the dependent variable (ROA)